Once Upon A Time in London - Han Amin (Manes Wordworks, 2025)
Ana Ibrahim prays five times a day and observes the holy month. Outside her solitary she had no special attachments. No friends and a family living continents away, just how she likes it. But under the seemingly innocent life lays an unforgotten past. There is someone she is quietly after, a deep-seated revenge that landed her in the theatre, a personal mission she was sure to accomplish. Until Matthew Forster comes along and threatens to bulldoze everything. When he was a child Matthew had lost a loved one to a plane hijack. Now having met Ana he is certain he doesn’t want anything to do with her until, a discovery of her private journal turns his world upside down. As he fights to keep his family together, he uncovers the truth about the woman he vows not to like. Once Upon a Time in London is a gripping tale of redemption, resilience, and love. Will they crash and burn, or find something worth fighting for in the wreckage?